Microcephaly is associated with impaired educational development in children with congenital heart disease - Constanze Pfitzer; Constanze Pfitzer; Constanze Pfitzer; Laura K. Sievers; Alina Hütter; Hashim-Abdul Khaliq; Martin Poryo; Felix Berger; Felix Berger; Felix Berger; Ulrike M. M. Bauer; Ulrike M. M. Bauer; et al. (Frontiers in Cardiovascular Medicine, 2022)
ObjectivesThis study aims to evaluate the school careers of patients with congenital heart disease (CHD) and microcephaly.MethodsAn exploratory online survey was conducted on patients from a previous study on somatic development in children with CHD in 2018 (n = 2818). A total of 750 patients participated in the online survey (26.6%). This publication focuses on 91 patients (12.1%) diagnosed with CHD and microcephaly who participated in the new online survey.ResultsMicrocephaly was significantly associated with CHD severity (p < 0.001). Microcephalic patients suffered from psychiatric comorbidity two times as often (67.0%) as non-microcephalic patients (29.8%). In particular, the percentage of patients with developmental delay, intellectual debility, social disability, learning disorder, or language disorder was significantly increased in microcephalic CHD patients (p < 0.001). A total of 85.7% of microcephalic patients and 47.6% of non-microcephalic patients received early interventions to foster their development. The school enrollment of both groups was similar at approximately six years of age. However, 89.9% of non-microcephalic but only 51.6% of microcephalic patients were enrolled in a regular elementary school. Regarding secondary school, only half as many microcephalic patients (14.3%) went to grammar school, while the proportion of pupils at special schools was eight times higher. Supportive interventions, e.g., for specific learning disabilities, were used by 52.7% of microcephalic patients and 21.6% of non-microcephalic patients.ConclusionPatients with CHD and microcephaly are at high risk for impaired educational development. Early identification should alert clinicians to provide targeted interventions to optimize the developmental potential.